2007
DOI: 10.1002/ana.21063
|View full text |Cite
|
Sign up to set email alerts
|

A second major histocompatibility complex susceptibility locus for multiple sclerosis

Abstract: ObjectiveVariation in the major histocompatibility complex (MHC) on chromosome 6p21 is known to influence susceptibility to multiple sclerosis with the strongest effect originating from the HLA-DRB1 gene in the class II region. The possibility that other genes in the MHC independently influence susceptibility to multiple sclerosis has been suggested but remains unconfirmed.MethodsUsing a combination of microsatellite, single nucleotide polymorphism, and human leukocyte antigen (HLA) typing, we screened the MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
114
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(123 citation statements)
references
References 56 publications
7
114
0
2
Order By: Relevance
“…However, when stratifying the results separately for all DRB1 alleles, Cw*05 conferred a significant protection for MS in the subgroup of individuals negative for DRB1*03. This is partially in line with the data reported by Yeo et al 11 who observed a protective effect of Cw*05 in the whole sample as well as in individuals negative for DRB1*03 and other MS-associated DRB1 alleles (DRB1*15, DRB1*0103). Conversely, in DRB1*03-positive individuals, and in the absence of A*02, Cw*05 was a risk marker and conferred a risk similar to DRB1*15 (OR ¼ 3.89, P ¼ 0.0006).…”
Section: Hla-class I Markers Involved In Ms Susceptibility L Bergamassupporting
confidence: 92%
See 2 more Smart Citations
“…However, when stratifying the results separately for all DRB1 alleles, Cw*05 conferred a significant protection for MS in the subgroup of individuals negative for DRB1*03. This is partially in line with the data reported by Yeo et al 11 who observed a protective effect of Cw*05 in the whole sample as well as in individuals negative for DRB1*03 and other MS-associated DRB1 alleles (DRB1*15, DRB1*0103). Conversely, in DRB1*03-positive individuals, and in the absence of A*02, Cw*05 was a risk marker and conferred a risk similar to DRB1*15 (OR ¼ 3.89, P ¼ 0.0006).…”
Section: Hla-class I Markers Involved In Ms Susceptibility L Bergamassupporting
confidence: 92%
“…(characterizing the 44.1 ancestral haplotype) was significantly decreased in the study of Yeo et al 11 However, the association with the A*02-B*44-Cw*05 haplotypic combination was not investigated by the authors. On the other hand, evidence reported in this study and from work undertaken using an experimental animal model 17 points to a direct role of A*02.…”
Section: Hla-class I Markers Involved In Ms Susceptibility L Bergamasmentioning
confidence: 85%
See 1 more Smart Citation
“…The strongest susceptibility signal maps to the HLA-DRB1 gene in the class II region of the major histocompatibility complex (MHC) (Barcellos et al, 2006;Yeo et al, 2007). Recently, the two largest genome-wide association studies (GWAS) of MS genetics confirmed HLA as the major MS susceptibility locus and provided unequivocal evidence for the association of additional 110 non-MHC "candidate" genetic variants conferring susceptibility to the disease (IMSGC, 2011;IMSGC, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…22,25 Best known among pathogens that tamper major histocompatibility complex class I expression are herpesviruses, which can alter T-and natural killer-lymphocyte function by subverting the expression of host major histocompatibility complex molecules, or by encoding viral homologues of these. [26][27][28][29][30][31] As all of the polymorphisms of the LRC in chromosome 19, natural killer cells, herpesviruses and HLA class I molecules have been implicated in the susceptibility or pathogenesis of MS, 8,[32][33][34][35][36][37][38][39] it is also of interest to determine whether the genotypic diversity of KIR is associated with MS and whether such an association could explain, by linkage disequilibrium (LD), the reported relationship between MS and deletion of LILRA3.…”
Section: Introductionmentioning
confidence: 99%